2016
DOI: 10.1155/2016/1840513
|View full text |Cite
|
Sign up to set email alerts
|

Low‐ω3 Fatty Acid and Soy Protein Attenuate Alcohol‐Induced Fatty Liver and Injury by Regulating the Opposing Lipid Oxidation and Lipogenic Signaling Pathways

Abstract: Chronic ethanol-induced downregulation of peroxisome proliferator-activated receptor gamma coactivator 1-alpha (PGC1α) and upregulation of peroxisome proliferator-activated receptor gamma coactivator 1-beta (PGC1β) affect hepatic lipid oxidation and lipogenesis, respectively, leading to fatty liver injury. Low-ω3 fatty acid (Low-ω3FA) that primarily regulates PGC1α and soy protein (SP) that seems to have its major regulatory effect on PGC1β were evaluated for their protective effects against ethanol-induced he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 66 publications
1
9
0
Order By: Relevance
“…Based on our previous single dose studies, we set the dose of 3% BLEx. The animal model was created according to the methods described by Reyes-Gordillo et al (Reyes-Gordillo et al, 2016). The serum AST, ALT, total protein, albumin levels, and A/G ratio, which are the indices of liver injury did not change when the rats were fed with 5% ethanol for 5 weeks, demonstrating that there was no ethanol-induced liver injury.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our previous single dose studies, we set the dose of 3% BLEx. The animal model was created according to the methods described by Reyes-Gordillo et al (Reyes-Gordillo et al, 2016). The serum AST, ALT, total protein, albumin levels, and A/G ratio, which are the indices of liver injury did not change when the rats were fed with 5% ethanol for 5 weeks, demonstrating that there was no ethanol-induced liver injury.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have established that a high ω -3 polyunsaturated fatty acid (PUFA) diet is more harmful in causing alcoholic liver injury than saturated fat diets [ 45 49 ]. We have previously shown that low ω -3 PUFA, but not high ω -3 PUFA, attenuates alcoholic liver injury [ 50 ]. Moreover, Chang et al have demonstrated that while there was no significant increase in serum AST and ALT levels in chow-fed mice that were administered with a single dose of ethanol (5 g/kg) gavage, there was a significant increase in the serum AST and ALT levels in high-fat diet fed mice that were administered with a single dose ethanol (5 g/kg) gavage [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on our previous single dose studies, we set the dose of 3% BLEx. The animal model was created according to the methods described by Reyes-Gordillo et al (Reyes-Gordillo et al, 2016). The serum AST, ALT, total protein, albumin levels, and A/G ratio, which are the indices of liver injury did not change when the rats were fed with 5% ethanol for 5 weeks, demonstrating that there was no ethanol-induced liver injury.…”
Section: Discussionmentioning
confidence: 99%